The Holocaust object in Polish and Polish-Jewish culture - Shallcross, Bożena 1952- (Indiana University Press, 2011)
On jouissance -- A dandy and Jewish detritus -- The material letter J -- On waste and matter -- Holocaust soap and the story of its production -- The guilty afterlife of the soma -- On contact -- The manuscript lost in Warsaw -- Things, touch, and detachment in Auschwitz -- Coda: the post-Holocaust object